2015
DOI: 10.1136/bmjspcare-2014-000826
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of ventilation at the patient's request in MND: a retrospective exploration of the ethical and legal issues that have arisen for doctors in the UK

Abstract: BackgroundVentilatory support has benefits including prolonging survival for respiratory failure in motor neurone disease (MND). At some point some patients may wish to stop the intervention. The National Institute of Health and Care Excellence (NICE) guidance recommends research is needed on ventilation withdrawal. There is little literature focusing on the issues doctors encounter when withdrawing ventilation at the request of a patient.AimTo identify and explore with doctors the ethical and legal issues tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 17 publications
0
44
0
7
Order By: Relevance
“…In the literature on WLTV in ALS, the focus had been on patients with TIV (15,18). Only recently, systematic data on WLTV in both NIV and TIV have been obtained (11,17). Rather than capturing the whole range of palliative concepts, our study compared ASC and CDS as being two distinct palliative approaches in WLTV (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature on WLTV in ALS, the focus had been on patients with TIV (15,18). Only recently, systematic data on WLTV in both NIV and TIV have been obtained (11,17). Rather than capturing the whole range of palliative concepts, our study compared ASC and CDS as being two distinct palliative approaches in WLTV (17).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying reasons for the steady rise in life-prolonging treatment with NIV or TIV are improved home ventilation, availability of electronic communication systems and the availability of online participatory activities (7,8). Both forms of long-term ventilation can be associated with a substantial psychosocial strain for the patients and caregivers resulting in the wish of the patient to withdraw from ventilation therapy (9)(10)(11). Typical factors contributing to the withdrawal of long-term ventilation (WLTV) are the burden of care, social deprivation or loss of the ability to communicate through an ALS-related ophthalmoplegia and locked-in syndrome (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health professionals in ALS care can experience varying degrees of stress related to their clinical work,94 and the emotional burden encountered by health care professionals caring for people with ALS can be severe 55. Feelings of stress and anxiety can arise for physicians while delivering the diagnosis and prognosis,72 whereas withdrawal of treatments can pose ethical and psychological dilemmas for health care professionals who provide end-of-life care 95,96. In an Australian-based study,72 70% of neurologists surveyed found communicating the diagnosis of ALS “very to somewhat difficult,” whereas 43% of them found responding to patients’ and family members’ reaction to the disclosure “very to somewhat difficult.” Sixty-five percent of neurologists experienced “high to moderate” stress and anxiety during the disclosure.…”
Section: Introductionmentioning
confidence: 99%
“…The Guidance has been endorsed by the Motor Neurone Disease Association, the Royal College of Nursing, the Royal College of Physicians of London, the Royal College of General Practitioners and Hospice UK, and is consistent with General Medical Council (GMC) standards of good practice,2 and is compatible with coronial law and principles. It has resulted from original research from Faull et al 3 in Leicester which explored the experiences of families and healthcare professionals and found that while there were examples of good practice, there was considerable variation in care and evidence of poor outcomes for patients, families and the professionals involved 4 5…”
mentioning
confidence: 99%